THE ROLE OF SPACE IN EU POLICIES AND THE REGIONALIZATION PROCESS (EU and comparative law issues and challenges series (ECLIC), 2018)
Space is one of the most debated issues related to the European Union policies. In terms of space, EU perpective is mainly focused on regions. Regions are, more or less succesfully the core of spatial approach of European project. The debate moves around different approaches. In a constitutive perspective, regionalization process aims to create more homogeneus partitions. Anyway, the inequalities are more often inside the regions than among regions. To overcome this limit of the traditional top-down regionalization many scholars propose different approaches, from the place-based (Barca, 2009) to the relational (Celata & Coletti, 2014). As it is proposed by Capello (2016), aspects of regional space should be studied in terms of location choices, productive and innovative capacity, competitiveness and relations with the local system. Some scholars (Stimson, Stough & Roberts, 2006) mention different traditional tools for measuring and evaluating regional economic performance. On the other hand there are some other approaches as well, for instance, Capello & Camagni (2008) give insight into forecasting as a way of implementing quantitative foresight (i.e. the MASSST model). Looking at the space in a performative perspective, according with the critical geography, regionalization has a pivotal role in many fields of social activities, such as identity and migration. So, in the European Union the regionalization can’t be considered as a collateral effect of economic or social goals. This paper aims to reconceptualize the controversial relation between EU policies and space. Go further to an iconic slogan “The Europe of Regions”, the article propones to contestualize how the space was included in the EU programmes. At the same time, it aims to analyze how space organization can be included in the EU activities, also in terms of relationship with the parameters often used to analyze regionalization.